Sex differences in primary malignant cardiac tumors: A multi‐institutional cohort study from National Cancer Database. Issue 5 (28th February 2022) - Rahouma, Mohamed; Baudo, Massimo; Shmushkevich, Shon; Chadow, David; Mohamed, Abdelrahman; Girardi, Leonard; Gaudino, Mario; Lorusso, Roberto
Abstract: Introduction: Despite the significant clinical importance of sex among factors affecting cancer progression and survival, it remains one of the least studied factors. Therefore, we sought to examine these differences in relation to primary malignant cardiac tumors (PMCTs) using a national data set. Methods: The 2004–2017 National Cancer Database was queried for patients with PMCTs. Annual trend of females' percent was assessed. Overall survival predictors were evaluated with Kaplan‐Meier and Cox‐regression. Subgroup analysis was done based on histology, comorbidity index, race, insurance, and surgical treatment. Results: PMCTs were identified in 736 patients (median age 52, female [47.8%]). Most of them were high‐grade (49.2%). About 60% underwent surgery. Angiosarcoma (43%), fibrosarcoma (5.2%), and leiomyosarcoma (5.2%) were the most common pathologies. Based on multivariate Cox‐regression, higher income, higher comorbidity index, angiosarcoma, and Stage III/IV were associated with higher late mortality, while year of diagnosis and use of surgery or chemotherapy were associated with lower mortality. Among the surgical group, age, higher income, higher comorbidity index, angiosarcoma, and Stage III/IV were independent predictors of higher late mortality, while private insurance and year of diagnosis were associated with lower late mortality. No difference was seen between males and females in 30‐day and late mortality ( p = .71). Subgroup analysis based on Cox‐regression showed no differences in late mortality between males and females. Conclusion: PMCTs have poor overall survival. Surgery and chemotherapy were associated with longer survival benefits. On the contrary, the associated risk factors for mortality were advanced age, higher comorbidity index, angiosarcoma histology, and Stage III/IV.